The structure of the γ-TuRC at the microtubule minus end: not just one solution - Gao, Qi; Vermeulen, Bram J. A.; Würtz, Martin; Shin, Hyesu; Erdogdu, Dilara; Zheng, Anjun; Hofer, Florian W.; Neuner, Annett; Pfeffer, Stefan; Schiebel, Elmar (Bioessays, 2024)
In cells, microtubules (MTs) assemble from α/β-tubulin subunits at nucleation sites containing the γ-tubulin ring complex (γ-TuRC). Within the γ-TuRC, exposed γ-tubulin molecules act as templates for MT assembly by interacting with α/β-tubulin. The vertebrate γ-TuRC is scaffolded by γ-tubulin-interacting proteins GCP2-6 arranged in a specific order. Interestingly, the γ-tubulin molecules in the γ-TuRC deviate from the cylindrical geometry of MTs, raising the question of how the γ-TuRC structure changes during MT nucleation. Recent studies on the structure of the vertebrate γ-TuRC attached to the end of MTs came to varying conclusions. In vitro assembly of MTs, facilitated by an α-tubulin mutant, resulted in a closed, cylindrical γ-TuRC showing canonical interactions between all γ-tubulin molecules and α/β-tubulin subunits. Conversely, native MTs formed in a frog extract were capped by a partially closed γ-TuRC, with some γ-tubulin molecules failing to align with α/β-tubulin. This review discusses these outcomes, along with the broader implications.